2016
DOI: 10.1027/0227-5910/a000423
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Suicide in LGBT Populations

Abstract: Specific predictive factors for suicide in LGBT populations in Australia were identified, including significantly poorer mental health outcomes and more violence across an array of measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…Our study identified two relational risk factors that are associated with greater suicide risk among all subgroups of sexual minorities in our sample. Building on the limited literature base (McDermott et al., ; Skerrett et al., ), we found that shame is one risk factor associated with greater suicide risk. This finding supports social constructionists framing of suicidality among sexual minorities, which focuses on the pressures and tensions of heterosexism and heternormativity in identity development and well‐being among sexual minorities (Cover, ; McDermott & Roen, ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our study identified two relational risk factors that are associated with greater suicide risk among all subgroups of sexual minorities in our sample. Building on the limited literature base (McDermott et al., ; Skerrett et al., ), we found that shame is one risk factor associated with greater suicide risk. This finding supports social constructionists framing of suicidality among sexual minorities, which focuses on the pressures and tensions of heterosexism and heternormativity in identity development and well‐being among sexual minorities (Cover, ; McDermott & Roen, ).…”
Section: Discussionmentioning
confidence: 71%
“…Although shame is strongly associated with psychological distress among sexual minorities (Mereish & Poteat, ), there is a dearth of literature examining the association between shame and suicide risk among sexual minorities. One study found that shame was one of the key factors associated with completed suicide among sexual minorities (Skerrett, Kõlves, & De Leo, ), and a qualitative study found that self‐destructive behaviors, including suicidality, functioned as a method to avoid shame related to heterosexist experiences (McDermott, Roen, & Scourfield, ). These studies underscore the possibility of shame as a mechanism through which minority stress may increase suicide risk; however, the mediating effects of shame on these associations have yet to be tested.…”
Section: Theoretical Models Explaining Suicide Risk Among Sexual Minomentioning
confidence: 99%
“…In much previous research, all sexual minorities are combined in one group due to small sample sizes (Bouris et al, 2016; Espelage et al, 2008; Hughes et al, 2010; Hughes et al, 2014; Skerrett et al, 2016). By using a large, nationally representative sample, we were able to investigate the relationship between specific subgroups of SMY and alcohol use.…”
Section: 0 Conclusionmentioning
confidence: 99%
“…However, a recent study reported higher odds of any lifetime mood disorder in sexual minority women who experienced discrimination compared with those who did not (3). The factors contributing to mood disorders in LGBT people may include a lack of acceptance by family and self that is reflected in internalized homophobia, shame, negative feelings about one's own sexuality/ gender, and uneasiness with one's own appearance (5).…”
Section: A Brief Discussion On Mood Disorders In the Lgbt Populationmentioning
confidence: 98%